Genetic diversity of Cryptosporidium spp. in non-human primates in rural and urban areas of Ethiopia - Ambachew W. Hailu; Abraham Degarege; Beyene Petros; Damien Costa; Yonas Yimam Ayene; Ven-ceslas Villier; Abdelmounaim Mouhajir; Loic Favennec; Romy Razakandrainibe; Haileeysus Adamu (PLoS ONE, 2022)
Non-Human Primates (NHPs) harbor Cryptosporidium genotypes that can infect humans and vice versa. NHPs Chlorocebus aethiops and Colobus guereza and humans have overlapping territories in some regions of Ethiopia, which may increase the risk of zoonotic transmission of Cryptosporidium. This cross-sectional study examined the molecular prevalence and subtypes of Cryptosporidium spp. from 185 fecal samples of Chlorocebus aethiops and Colobus guereza in rural and urban areas in Ethiopia. Samples were tested for Cryptosporidium infection using nested polymerase chain reaction (PCR), and subtypes were determined by sequencing a fragment of the 60-kDa glycoprotein gene (gp60). Of the 185 samples, fifty-one (27.56%) tested positive for Cryptosporidium infection. The species detected were C. parvum (n = 34), C. hominis (n = 12), and C. cuniculus (n = 3). Mixed infection with C. parvum and C. hominis were detected in 2 samples. Four C. hominis family subtypes (Ia, Ib, Id, and Ie) and one C. parvum family subtype (IIa) were identified. C. hominis IaA20 (n = 7) and C. parvum IIaA17G1R1 (n = 6) were the most prevalent subtypes detected. These results confirm that Chlorocebus aethiops and Colobus guereza can be infected with diverse C. parvum and C. hominis subtypes that can also potentially infect humans. Additional studies could help to understand the role of NHPs in the zoonotic transmission of Cryptosporidium in Ethiopia.